Infant and Child Diets of Hunter-Fisher-Gatherer Societies: A Systematic Review. (29th May 2020) - Reid, Miranda; Gyimah, Emmanuel; Dewey, Kathryn; Lutter, Chessa; Quinn, E A; Chapnick, Melissa; Iannotti, Lora
Abstract: Objectives: To identify key changes in child diets during the transition to agriculture by synthesizing evidence on 1) infant and child hunter-fisher-gatherer diets to identify common elements of an evolutionary child diet and 2) early agricultural groups. Methods: We searched five databases (Academic Search Complete via EBSCO, Anthropology Plus via EBSCO, Medline via PubMed, Scopus, and SocIndex with Full Text via EBSCO). Childhood was defined as children 10 years or younger. Early agriculture was defined as cultivation activities during the Neolithic or regional Neolithic equivalent era (e.g., Woodland Period), to account for the variation in the transition to agriculture. Studies examining hominins from the following species were eligible: Homo erectus/Homo ergaster, Homo neanderthalensis, Homo heidelbergensis, and Homo sapiens. We included peer-reviewed papers of qualitative, quantitative, and mixed methods on infant and childhood diets for groups whose primary subsistence method was hunting, fishing, or gathering or groups who were transitioning to early agriculture. Title and abstract reviews were conducted in Rayyan QCRI by two blinded authors. Discrepancies were reviewed by a third author. Full text review was also blinded. We scored studies with the Mixed Methods Appraisal Tool (2018), and we synthesized evidence using a narrative synthesis with sub-group analysis as appropriate. Results: The publications covered a range of subsistence groups and study types (e.g., ethnography, isotopic analysis). Groups from Africa, Asia, Europe, North America and South America were represented, and time periods ranged from the Mesolithic Era to present. Our analysis indicated a significant shift in child diet accompanying the shift to agriculture. Hunter-gatherer-fisher children had more varied diets with a larger proportion of animal-source foods during and after the complementary feeding period compared to early agricultural groups. Conclusions: Early agricultural diets, similar to current child dietary patterns, have diverged from the diets of hunter-fisher-gatherer children in important ways. These differences could offer insight into child feeding guidelines today. Funding Sources: This project was internally funded by the E3 Nutrition Lab at Washington University in St. Louis.